Nowy stary? When new is not new, or on lexical properties of one Polish expression vs. other expressions based on antonymic pairs - Wołk, Mariola (Papers in Linguistics, 2025)
The article concerns a two-part expression nowy stary (Eng. ‘new old’), e.g. ‘new old president,’ ‘new old rules,’ ‘new old couch.’ The expression causes problems as regards its spelling, yet they are still secondary to its lexical status. The aim of the undertaken research is to resolve both issues. The heterogeneous notation of the analysed sequence results from a variation in the way the two elements are combined (i.e. with a comma or a hyphen). Different variants of its spelling are in use – both with and without these marks. The decision related to implementing a particular spelling variant is significantly influenced by the lexical status of the described expression, i.e. whether it is an ad hoc, free combination of two adjectives (replaceable by any other ones), or whether it is a separate and – meaning-wise – indivisible unit (a unit of language the way Andrzej Bogusławski understands it). The article provides a comprehensive proposal for resolving the issues related to the lexicological description and notation of the presented sequence.